The first ninety years a Sumerian celebration in honor of Miguel Civil - Feliu, Lluís 1965-; Karahashi, Fumi; Rubio, Gonzalo; Civil, Miguel 1926-2019 (Boston Berlin De Gruyter, 2017)
This volume is dedicated to Miguel Civil in celebration of his 90th birthday. Civil has been one of the most influential scholars in the field of Sumerian studies over the course of his long career. This anniversary presents a welcome occasion to reflect on some aspects of the field in which he has been such a driving force
Bibliographie der Schriften Miguel Civils von 1991-2016: Seiten xvii-xix
Keywords: Sumerians -- History; Sumerians -- Antiquities; Festschrift; Aufsatzsammlung